Geometric Modeling and Contact Characteristic Analysis of Hindley Worm and Cylindrical Helical Gear Transmission - Zhao Chaofei; Wei Bingyang (Jixie chuandong)
A kind of Hindley worm and cylindrical helical gear is presented. According to the geometrical parameters of Hindley worm,the geometric parameters of the helical gear with the Hindley worm is calculated,a three-dimensional model of Hindley worm and cylindrical helical gear is established. The statics analysis is carried out by using the finite element Workbench software,the tooth surface contact stress,equivalent stress and displacement are obtained. The tooth profile and helical double direction concave are modified for helical gear. The results show that the concave modification can reduce the contact stress and displacement of the tooth surface properly,so as to improve the bearing capacity of gear pair. The effect of tooth profile modification on contact performance is more significant. The feasibility of the proposed straight Hindley worm and helical gear transmission is verified by processing and rolling test.